Estimation of car braking parameters - Radavičius, Marijus; Nagurnas, Saulius (Lietuvos matematikos rinkinys, 2004)
In the paper the problem of prediction of car braking distance from its initial speed is considered. Based on the data of braking experiments, a regression model is fitted and validated and the covariance structure of the prediction errors is established.
Keywords: car braking distance; deceleration; general linear mixed model; repeated measures; regression analysis